Tinjauan Yuridis Pelanggaran terhadap Kedaulatan Teritorial Venezuela oleh Amerika Serikat dalam Perspektif Hukum Internasional - Romadhon, Wahyu Fajar; Paramita, Pinastika Prajna; Na’im, Mohammad Imamin (RechtJiva, 2026)
This study examines the legality of the United States military operations against Venezuela and the arrest of Venezuelan President Nicolás Maduro in January 2026 from the perspective of International Law. It aims to analyze whether these actions violate the principles of state sovereignty, territorial integrity, the prohibition on the use of force, and the immunity of heads of state.  The research employs a normative juridical method with statutory, conceptual, and case-based approaches. The legal materials consist of international treaties, UN resolutions, judgments of the International Court of Justice, and legal doctrines.  The findings indicate that the United States’ military operation constitutes an unlawful use of force under Article 2(4) of the UN Charter and cannot be justified under Article 51 concerning the right of self-defense. The arrest of Nicolás Maduro also contradicts the principles of territorial sovereignty, non-intervention, and immunity ratione personae of a sitting head of state.  Accordingly, the actions of the United States can be categorized as a military intervention that violates fundamental principles of International Law. This study contributes to the development of International Law by clarifying the legal limits of the use of force and extraterritorial law enforcement against foreign heads of state, and by affirming that combating transnational crime cannot override the fundamental principles of International Law.